Association between physiological falls risk and physical performance tests among community-dwelling older adults - Singh DK (Dove Medical Press, 2015)
Devinder KA Singh,1 Sharmila GK Pillai,1 Sin Thien Tan,1 Chu Chiau Tai,1 Suzana Shahar2 1Physiotherapy Programme, School of Rehabilitation Sciences, 2Nutrition and Dietetics Programme, School of Healthcare Sciences, Faculty of Health Sciences, Universiti Kebangsaan Malaysia, Jalan Raja Muda Abdul Aziz, Kuala Lumpur, Malaysia Background: Physical performance and balance declines with aging and may lead to increased risk of falls. Physical performance tests may be useful for initial fall-risk screening test among community-dwelling older adults. Physiological profile assessment (PPA), a composite falls risk assessment tool is reported to have 75% accuracy to screen for physiological falls risk. PPA correlates with Timed Up and Go (TUG) test. However, the association between many other commonly used physical performance tests and PPA is not known. The aim of the present study was to examine the association between physiological falls risk measured using PPA and a battery of physical performance tests.Methods: One hundred and forty older adults from a senior citizens club in Kuala Lumpur, Malaysia (94 females, 46 males), aged 60 years and above (65.77±4.61), participated in this cross-sectional study. Participants were screened for falls risk using PPA. A battery of physical performance tests that include ten-step test (TST), short physical performance battery (SPPB), functional reach test (FRT), static balance test (SBT), TUG, dominant hand-grip strength (DHGS), and gait speed test (GST) were also performed. Spearman’s rank correlation and binomial logistic regression were performed to examine the significantly associated independent variables (physical performance tests) with falls risk (dependent variable).Results: Approximately 13% older adults were at high risk of falls categorized using PPA. Significant differences (P<0.05) were demonstrated for age, TST, SPPB, FRT, SBT, TUG between high and low falls risk group. A significant (P<0.01) weak correlation was found between PPA and TST (r=0.25), TUG (r=0.27), SBT (r=0.23), SPPB (r=-0.33), and FRT (r=-0.23). Binary logistic regression results demonstrated that SBT measuring postural sways objectively using a balance board was the only significant predictor of physiological falls risk (P<0.05, odds ratio of 2.12).Conclusion: The reference values of physical performance tests in our study may be used as a guide for initial falls screening to categorize high and low physiological falls risk among community-dwelling older adults. A more comprehensive assessment of falls risk can be performed thereafter for more specific intervention of underlying impairments. Keywords: balance, postural sways, agility, mobility, strength, gait speed